comparative photostability study of fancimef tablet and it's active ingredients (1999)
fancimef tablet is one of the multi-component drugs recently introduced into malaria theraphy to combat the resistent strains of plasmodium parasite. Like most complex organic compounds, it is expectesd that the organic compounds in Fancimf tablet will absorb light spectra leading to its photodecomposition and all its attendant problems. In this study, a comparative photostability study of the Fancimf tablet and its active components was undertaken. The results obtained showed that the active ingredients of Fancimf tablet undergo photodecomposition in buffer solutions while the dry Fancimf tablet (powder) is photostable. Thus suggesting that Fancimf tablet is not susceptible to photodecomposition.